Mathematics teaching in dialog with authors of education philosophy (FAVE Sección Ciencias Veterinarias, 2017)
For several years in the School of Veterinary Medicine of Universidad Nacional del Litoral, a team of teachers-researchers of Mathematics works on a proposal of "Collaborative Learning" in which are stimulated and evaluated social skills essential for a correct interaction. In this article, we try to talk with some authors of texts of philosophy, in which issues related to communication, language, symbol, meaning and pleasure are raised, from which aspects related to the aforementioned social competences are revealed. In Mathematics, communication and language refer to the use of words and symbols whose meaning is different according to the context in which they are used, and the meaning attributable to a word / symbol may be quite different in mathematics than in everyday language. At the end of the article it is mentioned, how meaning and pleasure portray who the students are, how they see themselves, and how they construct a particular vision of their future.
Keywords: mathematics; social skills; collaborative learning